World congresses of sociology: history and modernity - Titarenko, Larissa G. (Journal of the Belarusian State University. Sociology, 2023)
The article discusses the problems of history of the development of the International Sociological Association. The goals of this organisation, its composition, and activities are revealed. The role of international sociological congresses, at which participants from different countries present their scientific achievements to their colleagues, is briefly outlined. The role of Soviet and post-Soviet sociologists in the functioning of the International Sociological Association and in congresses is revealed. The article analyses the topics of the XX International Sociological Congress (2023 June 25 – July 1), which put forward the idea of dialogic sociology. The objectives of the article are also to identify the connection between congresses and the preservation of the theoretical and organisational dominance of sociology of leading Western countries. It is concluded that the change in leadership and theoretical perspectives of the International Sociological Association goes slow and occurs in conditions of global uncertainty and conflict.